(untitled) - Wright, Gary

Demonstrating the value of case histories towards the improvement of knowledge and understanding of geotechnical problems using slope stability back-analysis. (Stellenbosch : Stellenbosch University, 2024)
Thesis (MEng)--Stellenbosch University, 2024.